2013
DOI: 10.2528/pierc13053006
|View full text |Cite
|
Sign up to set email alerts
|

A Compact Wideband Bandpass Filter Using Novel CSRR Loaded Qmsiw Resonator With High Selectivity

Abstract: Abstract-A novel quarter-mode substrate integrated waveguide (QMSIW) resonator with back-to-back triangular complementary split-ring resonators (CSRRs) etched on the waveguide surface is proposed in this paper. The proposed CSRR structures allow the implementation of a forward-wave passband propagating with high selectivity below the characteristic cutoff frequency of the conventional QMSIW. Utilizing the property of flexible open structure on QMSIWs' two sides, a cascaded quadruplet (CQ) bandpass filter (BPF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The emerging substrate integrated waveguide (SIW) technique has gained renewed attention for the integration of planar and non-planar circuits into a simple and low-cost PCB or LTCC fabrication process [ 1 , 2 ]. Then, the traditional waveguide, which is costly with a bulky non-planar hollow rectangular structure and high power capacity, can be synthesized into a planar substrate with metalized slots or even arrays of metallic via posts.…”
Section: Introductionmentioning
confidence: 99%
“…The emerging substrate integrated waveguide (SIW) technique has gained renewed attention for the integration of planar and non-planar circuits into a simple and low-cost PCB or LTCC fabrication process [ 1 , 2 ]. Then, the traditional waveguide, which is costly with a bulky non-planar hollow rectangular structure and high power capacity, can be synthesized into a planar substrate with metalized slots or even arrays of metallic via posts.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it was demonstrated that the split ring resonator SRR has a very narrow band response compared to the complementary split ring resonator [11]. Recently, complementary split ring resonator is more frequently used for the design of filters with wide and deep stopbands [12][13][14][15]. Band-reject filters were as well designed based on the defected ground structure (DGS) technology [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Many efforts have been exerted to design filters using SIW, HMSIW and HMFSIW cavities [3]- [5]- [6] at difference frequencies with and without cross coupling [7]- [8]- [9]- [19] to give different responses, filters designed were with different cavities shapes, circular, triangular, square [10]- [11]- [12]- [13], loaded or not loaded, single or multi-mode and other types [14]- [15]- [16]- [26].…”
Section: Introductionmentioning
confidence: 99%